2014
DOI: 10.1002/cpp.1906
|View full text |Cite
|
Sign up to set email alerts
|

The Metacognitions about Symptoms Control Scale: Development and Concurrent Validity

Abstract: Objective: This paper presents the development and preliminary validation of a self-report instrument designed to measure metacognitions pertaining to symptoms control in the form of: (1) symptoms focusing; and (2) Regression analysis revealed that positive and negative metacognitions about symptoms control significantly predicted fatigue severity when controlling for anxiety and depression. Conclusions:The newly developed instrument may help future research that examines the role of metacognitions in CFS, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…The MCQ‐30 measures general metacognitive constructs that do not directly and specifically address pain. Use of targeted measures of metacognition, such as the metacognitions about Symptom Control Scale (Fernie et al., ), may reveal findings disparate from those reported here. Additionally, while the cross‐sectional nature of our results does not allow us to determine whether metacognitive beliefs and pain catastrophizing can be considered distinct therapeutic targets, this study provides evidence that metacognitive processes have implications at the daily level, and their effects in our analyses may be best interpreted as a more stable marker of poor psychological adjustment to pain.…”
Section: Discussioncontrasting
confidence: 79%
“…The MCQ‐30 measures general metacognitive constructs that do not directly and specifically address pain. Use of targeted measures of metacognition, such as the metacognitions about Symptom Control Scale (Fernie et al., ), may reveal findings disparate from those reported here. Additionally, while the cross‐sectional nature of our results does not allow us to determine whether metacognitive beliefs and pain catastrophizing can be considered distinct therapeutic targets, this study provides evidence that metacognitive processes have implications at the daily level, and their effects in our analyses may be best interpreted as a more stable marker of poor psychological adjustment to pain.…”
Section: Discussioncontrasting
confidence: 79%
“…Fernie et al 2014). Thirty-four participants reported that they had undergone psychotherapy previously that is not on going.…”
Section: Methodsmentioning
confidence: 99%
“…One participant noted the inability to control the thoughts (#5), another (#6) increasing stress, and one a negative impact on concentration (#9). Negative SF metacognitions pertained to an increased awareness of symptoms leading to an increase in their severity (#2), a worsening of mood (#3, 7,9), and a restriction of activities (#10). One participant's negative SF metacognition related to the risk of believing they were experiencing an off-period when they were not (#7).…”
Section: Nature Of Metacognitionsmentioning
confidence: 99%
“…Nine participants described positive CTS metacognitions and three SF metacognitions. The most common theme of the positive CTS metacognitions concerned beliefs about controlling or coping better with symptoms including motor fluctuations (participants #1, 3,4,6,7,9,10) with one participant taking it as a signifier of strength of character (#2). Positive SF metacognitions again related to beliefs about better control over symptoms but less consistently than for CTS (#7,10).…”
Section: Nature Of Metacognitionsmentioning
confidence: 99%
See 1 more Smart Citation